PENGARUH KUALITAS DATA TERHADAP MANFAAT YANG DIPEROLEH DARI IMPLEMENTASI DATA WAREHOUSE - Munawar, Munawar (Lembaga Penerbitan Universitas Esa Unggul, 2017)
Given that the literature indicates that many benefits can be obtained from a DW (data warehouse), but that the threat of failure is also high, therefore more understanding of the quality dimensions that contribute to the success of a DW is required. This study address that need through an empirical investigation of success in data warehousing as measured by DQ (data quality) dimensions involvement in every stage of DW development. This study attempts to confirm DW benefits from reviewed literature in five case studies and three consultants. This study also identifies relationship amongst DQ dimensions in DW development stages and DW success. This study is helpful for DW practitioners, implementers and researchers for understanding of the challenges which DQ dimensions in DW stages are significant to establishing a successful DW development.Keywords: data warehouse, data quality, data warehouse benefits.Abstrak